2010
DOI: 10.1007/s11695-009-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gastric Banding Is Safe in Outpatient Surgical Centers

Abstract: The ability to treat patients within 4 h and the extremely low complication rates reported here contribute to a growing literature supporting the safe performance of LAGB in an outpatient setting for the treatment of morbid obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
4
30
0
Order By: Relevance
“…There was no association between higher BMI and non-ambulatory LAGB outcomes. This finding is supported by similar findings of Cobourn et al in a series of 1,641 patients (18).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There was no association between higher BMI and non-ambulatory LAGB outcomes. This finding is supported by similar findings of Cobourn et al in a series of 1,641 patients (18).…”
Section: Discussionsupporting
confidence: 89%
“…The 2006 American Society of Anesthesiologists practice guidelines for perioperative management of patients with OSA were developed with the aim to help practitioners make rational decisions and provide optimal perioperative care to those patients (17). However, some practitioners do not consider appropriately treated as a contraindication for ambulatory LAGB (6,18). Such an approach is actually supported by this study that demonstrated similarities in non-ambulatory (39.1%) and ambulatory outcomes (37.4%) of patients with OSA (p=0.83).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The standardized pars flaccida technique was used. 17 The band reservoir was gradually filled with 6.5 mL of saline. The band reservoir was additionally filled with 2 mL of saline in the 4th and 8th week after the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…83,84 LAGB surgery generally has a low risk of mortality and morbidity. 40 Mortality rates are on the order of 1:1000 to 3000, which is comparable to or lower than that of common abdominal procedures such as appendectomy and cholecystectomy.…”
Section: Safety Early To 1 Yearmentioning
confidence: 99%